2013
DOI: 10.1038/ncomms3843
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry breaking in a mechanical resonator made from a carbon nanotube

Abstract: Nanotubes behave as semi-flexible polymers in that they can bend by a sizeable amount. When integrating a nanotube in a mechanical resonator, the bending is expected to break the symmetry of the restoring potential. Here we report on a new detection method that allows us to demonstrate such symmetry breaking. The method probes the motion of the nanotube resonator at nearly zero-frequency; this motion is the low-frequency counterpart of the second overtone of resonantly excited vibrations. We find that symmetry… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 41 publications
(86 reference statements)
2
55
2
Order By: Relevance
“…It should also be noted that an asymmetric beam shape in doubly clamped beams of nanometric dimensions is by no means an uncommon phenomena. In CNT resonators, it has been recently shown that such asymmetries are responsible for some particular features of their electromechanical response 31 . In the case of Si beams, top-down fabrication methods can be engineered to predetermine the amount of beam deflection at rest to target specific read-out signal levels.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that an asymmetric beam shape in doubly clamped beams of nanometric dimensions is by no means an uncommon phenomena. In CNT resonators, it has been recently shown that such asymmetries are responsible for some particular features of their electromechanical response 31 . In the case of Si beams, top-down fabrication methods can be engineered to predetermine the amount of beam deflection at rest to target specific read-out signal levels.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that low Q factors could originate from thermally induced spectral broadening 19 , clamping losses [20][21][22] or from symmetry breaking 23 . Until now, reports of the quality factor in CNTs have been based only on spectral measurements 14,18,24 .…”
mentioning
confidence: 99%
“…Considerable research is being conducted toward understanding the nonlinear dynamics of nanobeams, 5 nanotubes, nanowires, and graphene based resonators. 6 Moreover, various dynamical aspects in NEMS resonators, such as bifurcations, 7 nonlinear damping, 8 and chaos, 9 are studied to understand their characteristics and utilize them for real life applications.…”
Section: The Manuscriptmentioning
confidence: 99%